The Participant Journey Map: Understanding the Design of Interactive Augmented Play Spaces - Mast, Danica; de Vries, Sanne I.; Broekens, Joost; Verbeek, Fons J. (Frontiers in Computer Science, 2021)
Augmented Play Spaces (APS) are (semi-) public environments where playful interaction is facilitated by enriching the existing environment with interactive technology. APS can potentially facilitate social interaction and physical activity in (semi-)public environments. In controlled settings APS show promising effects. However, people’s willingness to engage with APS in situ, depends on many factors that do not occur in controlled settings (where participation is obvious). To be able to achieve and demonstrate the positive effects of APS when implemented in (semi-)public environments, it is important to gain more insight in how to motivate people to engage with them and better understand when and how those decisions can be influenced by certain (design) factors. The Participant Journey Map (PJM) was developed following multiple iterations. First, based on related work, and insights gained from previously developed and implemented APS, a concept of the PJM was developed. Next, to validate and refine the PJM, interviews with 6 experts with extensive experience with developing and implementing APS were conducted. The first part of these interviews focused on influential (design) factors for engaging people into APS. In the second part, experts provided feedback on the concept PJM. Based on the insights from the expert interviews, the PJM was adjusted and refined. The PJM consists of four layers: Phases, States, Transitions and Influential Factors. There are two overarching phases: ‘Onboarding’ and ‘Participation’ and 6 states a (potential) participant goes through when engaging with an APS: ‘Transit’, ‘Awareness’, ‘Interest’, ‘Intention’, ‘Participation’, ‘Finishing’. Transitions indicate movements between states. Influential factors are the factors that influence these transitions. The PJM supports directions for further research and the design and implementation of APS. It contributes to previous work by providing a detailed overview of a participant journey and the factors that influence motivation to engage with APS. Notable additions are the detailed overview of influential factors, the introduction of the states ‘Awareness’, ‘Intention’ and ‘Finishing’ and the non-linear approach. This will support taking into account these often overlooked, key moments in future APS research and design projects. Additionally, suggestions for future research into the design of APS are given.